Does One Leg Standing Duration Have Relation With GMFM Scores and Stability in Stance Phase for Hemiplegic Children ? - N. Ekin Akalan; Halenur, Evrendilek; Karaca, Gülşah; Bilgili, Fuat; Ertürk, Gamze (My University, 2018)
This paper reports the results of a study to validate a measure of gross motor function in detecting change in the motor function of disabled children. Physiotherapists used this instrument to assess 111 patients with cerebral palsy, 25 with head injury and 34 non-disabled preschool children on two occasions, the second after an interval of four to six months. Parents and therapists independently rated the children's function within two weeks of each assessment, and a sample of paired assessments was videotaped for 'blind' evaluation by therapists. Correlations between scores for change on this measure and the judgments of change by parents, therapists and 'blind' evaluators supported the hypothesis that the instrument would be responsive to both negative and positive changes.